(untitled) (Lex localis - Journal of Local Self-Government, 2020)
Public administration reforms in transition countries of Eastern Europe have gained considerable attention from researchers and practitioners in the recent decades. The main reason for this interest has been the fact that public administration transformation is closely related to the overall process of transition from planned economy and socialism to market economy and capitalism. Public administration has been considered one of the key institutional aspects in modern economies and societies, including the former socialist states of Eastern Europe. According to the neoinstitutional theoretical framework, changes of formal institutions (including public administration) are deeply embedded in informal institutions or culture (represented by informal norms and values). The main aim of the paper has been to explain unsuccessful reforms of public administration in postsocialist Serbia utilizing the propositions of the neoinstitutional approach developed by Richard Scott. The analysis has focused on normative institutional elements – informal norms and values. The survey on a nationally representative sample of citizens of Serbia was conducted in 2016, on the basis of the GLOBE theoretical and methodological principles. The study has confirmed the initial assumption about normative institutional elements (informal norms and values) as the most important obstacles for public administration reforms in Serbia.